Balance Impairments in Adolescents Post‐Sports Concussion during Single and Dual Tasks - Abdulaziz A. Alkathiry; Anthony P. Kontos; Joseph M. Furman; Susan L. Whitney; Saud F. Alsubaie; Patrick J. Sparto (Brain and Behavior, 2025)
ABSTRACT Objective This study aimed to explore changes in sway during single tasks and dual tasks in adolescents with and without sport concussion (SC). Methods A cross‐sectional study of 57 adolescents with an SC and 67 healthy participants was compared on static balance during single‐ and dual‐task conditions on hard and compliant surfaces. Postural sway was assessed using a force platform (with and without a foam pad) during three cognitive conditions. Results Individuals with SC had greater sway compared with healthy participants (p < 0.05). There were no significant interactions of groups and the task conditions. Across both groups, higher sway was observed in the compliant surface condition compared with the hard surface condition (p < 0.001). Greater sway was measured in the single task compared with the dual‐task conditions (p < 0.05), and the perceptual inhibition task generated greater sway than the spatial discrimination task (p < 0.05). Discussion Several factors were associated with increased sway, including compliant surface, dual task, and perceptual inhibition tasks. However, the root‐mean‐square in the anteroposterior direction was the only measure that showed a difference between the two groups, while only the normalized path length sway measures illustrated the difference between the dual‐ and single‐task conditions.